Operationalizing Organizational Strategy: Toward an Integrative Framework - Ginsberg, Ari (Academy of Management Review, 1984)
In order to aid the researcher in understanding the dynamics of the operationalization of organizational strategy, an analytical framework based on a systems perspective is developed. By identifying the key dimensions that represent the "input", "throughput", and "output" aspects of the operationalization process, this framework purports to facilitate a unified basis for comparing and integrating various approaches to the measurement of organizational strategy.